Improving Fine Motor Skills of Kindergarten Children Through 5M+PLAMS Activities at Aisyiyah Kindergarten Bustanul Athfal A - Wardana, Amelia Rizka; Prayogo, Basuki Hadi; Suwargono, Trio (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study aims to improve children’s fine motor skills through a variety of activities such as cutting, pasting, folding, drawing, coloring, and playing with magic sand in Group A of Aisyiyah Bustanul Athfal Kindergarten for the 2024/2025 academic year. This research is grounded in the importance of fine motor skills for academic readiness and life skills in early childhood. A Classroom Action Research (CAR) design was employed, involving two cycles and 12 children as subjects. Data collection techniques included observation, documentation, and informal interviews, with data analyzed using descriptive quantitative methods by calculating achievement percentages. The pre-cycle results showed 66.67% of children were in the “Emerging” category and 33.33% in the “Developing as Expected” category. After the first cycle, the results improved to 41.67% in the “Very Well Developed” category and 58.33% in the “Developing as Expected” category. In the second cycle, results significantly increased, with 83.33% of children classified as “Very Well Developed.” These results demonstrate that varied fine motor activities are effective in enhancing children's skills. It is recommended that teachers use similar activity variations, and further research should explore other developmental aspects.